2004
DOI: 10.1097/01.asn.0000141313.84470.4b
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin A Receptor Antagonism and Angiotensin-Converting Enzyme Inhibition Are Synergistic via an Endothelin B Receptor–Mediated and Nitric Oxide–Dependent Mechanism

Abstract: Abstract. Animal studies suggest that endothelin A (ETA) receptor antagonism and angiotensin-converting enzyme (ACE) inhibition may be synergistic. This interaction and the role of ETB receptors and endothelial mediators were investigated in terms of systemic and renal effects in humans in two studies. In one study, six subjects received placebo, the ETA receptor antagonist BQ-123 alone, and BQ-123 in combination with the ETB receptor antagonist BQ-788 after pretreatment with the ACE inhibitor enalapril (E) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 47 publications
(50 reference statements)
0
34
1
1
Order By: Relevance
“…[27][28][29] Furthermore, we have shown recently that acute ET A receptor antagonism can reduce proteinuria by an additional Ϸ30% on top of that achieved with optimal treatment with inhibitors of the renin-angiotensin system in subjects with proteinuric CKD. 14 The current study suggests that these effects are maintained longer term and are of a similar magnitude.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] Furthermore, we have shown recently that acute ET A receptor antagonism can reduce proteinuria by an additional Ϸ30% on top of that achieved with optimal treatment with inhibitors of the renin-angiotensin system in subjects with proteinuric CKD. 14 The current study suggests that these effects are maintained longer term and are of a similar magnitude.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the kidneys, when ET A receptor antagonism is given in the presence of ACE inhibition in healthy subjects, contrary to a lack of effect of ET A receptor antagonism alone, an increase in RBF and natriuresis is observed, an effect that seems to be both ET B dependent and NO mediated (53). Although it is tempting to attribute the increase in sodium excretion to the activity of an unblocked tubular ET B receptor, it is possible that the natriuresis is entirely a consequence of the renal vasodilation and so essentially a hemodynamic effect.…”
Section: Blockade Of the Et System And Ras: A Potential Synergismmentioning
confidence: 98%
“…Also, many clinical studies using ET receptor antagonists in patients with heart failure demonstrated major additional hemodynamic effects (153,154) in patients who already were receiving ACE inhibitors. Synergism with respect to acute systemic hemodynamic effects between ET A receptor antagonists and angiotensin receptor type 1 antagonists (ARB) (51) or ACE inhibitors (53) has been demonstrated in humans. More recently, the combination of ET receptor antagonism and ACE inhibition has been shown to improve endothelial function (155,156).…”
Section: Blockade Of the Et System And Ras: A Potential Synergismmentioning
confidence: 99%
“…Thus, based on this work, we hypothesized that, in patients with nondiabetic proteinuric CKD, selective ET A receptor antagonism would reduce proteinuria and arterial stiffness and improve endothelial dysfunction and that these effects would be greater than those achieved with BP reduction alone. Because we have previously demonstrated a synergism between ACE inhibitors and selective ET A receptor antagonism in health, 19 we anticipated that these effects might be evident on top of standard treatment with ACE inhibitors and/or angiotensin receptor blockers.…”
mentioning
confidence: 99%